一种通用且可配置的网络流量测量系统 (2022)
本发明属于以太网通信领域，涉及网络流量测量，具体为一种通用且可配置的网络流量测量系统，即能解决采用Netflow方案中对重要资源的占用率过大且无法对网络流做到精细化测量的问题，又能解决传统基于处理器的软件测量方法带来的资源开销大、处理时延大的问题。本发明测量包括：测量控制器与数据采集点组成，数据采集点由MAC控制逻辑和规则过滤引擎构成，MAC控制逻辑用于实现交换机与计算机之间的双向通路、以及数据采集点与测量控制器之间的通信；本发明测量控制器可更改网络参数(自定义匹配规则)，通过指令的形式下发给规则过滤引擎，从而实现对不同的流进行测量，配置灵活且支持通配符；并且处理速度快、测量精度高。 The invention belongs to the field of Ethernet communication, and relates to network traffic measurement, in particular to a universal and configurable network traffic measurement system, which not only can solve the problems of overlarge occupancy rate of important resources and incapability of performing refined measurement on network traffic in a Netflow scheme, but also can solve the problemsof large resource overhead and large processing delay caused by a traditional software measurement method based on a processor. The universal and configurable network traffic measurement system comprises a measurement controller and a data acquisition point, wherein the data acquisition point is composed of MAC control logic an